LITERATURE STUDY: THE CONCEPT OF LEADERSHIP IN ISLAMIC PERSPECTIVE - Alief Hafid Sidiq; Syaiful Anwar; Erna Herlina; Terien Rivaldo; Muhammad Rizko (CV. Four Son Scholarship, 2024)
Leadership plays a crucial role in shaping the direction and success of communities and organizations. In the Islamic context, leadership is seen as more than just a managerial responsibility; it touches on a deep spiritual and ethical dimension. This article explores the discourse on leadership in a variety of viewpoints, including politics, economics, and the ideologies of capitalism and socialism. This article specifically focuses its study on the perspective of Islamic leadership, by elaborating the verses of the Qur'an thematically. The author argues that the teachings of Islam play a strategic role in shaping the ideals of Justice, benefit, and truth. Leadership based on Shari'ah is believed to prevent leaders from personal or group interests that undermine commitment to truth and Justice, which will ultimately bring benefits to the community they lead. This research reinforces the understanding of the concept of leadership in Islam and serves as a guide for individuals who exercise leadership roles in Muslim societies. Muhammad, in Leadership in Islam: a Comprehensive Guide, emphasizes that it is important to integrate Islamic principles with good leadership practices, so